The Effect of Career Development, Integrity, and Work Motivation on Employee Performance - Lina Agustina; Syamsyir syamsyir (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This achievement of career development indicators backgrounds this research aims to 1) analyze the influence of career development on employee performance and 2) To analyze the influence of integrity on employee performance. 3) To analyze the influence of work motivation on employee performance. 4) To analyze the influence of career development on work motivation. 5) To analyze the effect of integrity on integrity on work motivation. The population is not larger than 100 respondents, so the researchers took 100% of the total population in the Padang Panjang City BKPSDM, namely 42 respondents with saturated sampling techniques. The data analysis technique used in this study is quantitative analysis. The data collected in this study were taken from two sources, namely primary and secondary data. Hypothesis testing in this study was carried out by path analysis. Based on the analysis and discussion results, it is known that 1) Career development has a positive and significant effect on employee performance and 2) Integrity has a positive and significant effect on employee performance. 3) Work motivation positively and significantly affects employee performance at the Development Personnel Agency. 4) Career development positively and significantly affects employee work motivation.5) Integrity has a positive and significant effect on employee workKeywords: career development, integrity, work motivation, employee performance